Prediction of Mental Health based on Emotional Alexithymia and Marital Burnout of Women Affected by Infidelity - Ghasemi, Hamideh; Demehri, Farangis; Abooei, Azadeh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to predict mental health based on emotional alexithymia and marital burnout of women affected by infidelity. Method: The current research was descriptive of predictive correlation type. The statistical population of the present study included women who referred to the counseling centers of District 5 of Tehran with a history of marital infidelity in 2022. According to the conducted research, 150 women visited the counseling centers of District 5 of Tehran in a period of 3 months, and 108 women were considered as a statistical sample through random sampling and Morgan's table. The research tools were Goldberg mental health questionnaires (1972), Toronto Alexithymia Scale (1994) and Pines marital burnout (2002). Kolmogorov-Smirnov test, Pearson correlation coefficient and multiple regression were used to analyze the data. Results: The results showed that the correlation coefficient between mental health and alexithymia is (0.380) and between mental health and marital burnout (0.568), which shows that there is a correlation between mental health and alexithymia and marital burnout of women affected by infidelity at the error level of 0.1. 0 and with 99 percent confidence, there is a significant positive and direct relationship. Also, regression analysis showed that emotional alexithymia and marital burnout have an effect on the mental health of women affected by infidelity (p